Medical Devices of the Abdomen and Pelvis and Their Complications: A Radiologic Atlas - Yaewon Jeong; Jongmee Lee; Kyeong Ah Kim; Cheol Min Park (대한영상의학회지, 2020)
A variety of medical devices have evolved throughout the years. Commonly used devices have typical radiological appearances which are familiar to radiologists. However, some new devices, as well as devices that are not commonly used, may be missed or misinterpreted by radiologists. It is even more difficult to identify a certain medical device with limited clinical history. Therefore, accurate identification of medical devices is crucial to diagnose malposition and potential complications. In this article, we provide a pictorial review of medical devices of the abdomen and pelvis according to classifications that include gastrointestinal devices, hepatobiliary devices, genitourinary devices, and miscellaneous. We also comprehensively review the clinical and radiologic features of complications related to these medical devices.